Narrowing the skill and knowledge gaps of young researchers on pest surveillances, diagnostics and integrated pest and disease management on wheat and food legumes in East Africa and CWANA regions - Kemal, Seid Ahmed; Kumari, Safaa; Boulamtat, Rachid (International Center for Agricultural Research in the Dry Areas, 2023)
Many young researchers working in plant protections lacks skills and knowledge on pest and disease surveillances, identification, disease/pest measurements, pest and disease dynamics, Integrated Pest and Disease Management (IPDM) options and different aspects of conducting plant protection research and generating quality results. Skill and knowledge gaps are pronounced mainly on emerging and new diseases, new pathogen pathotypes and races affecting food legumes. In addition, the training help researchers to evaluate breeding lines together with breeders in their respective countries. The training in 2023 cropping season included supporting MSc and PhD students to conduct parts of their Theses Research, internship and tailor-made group training to NPPOs, young researchers from countries in East Africa and CWANA regions.